2023
DOI: 10.1161/strokeaha.122.041502
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Disability: Association Between Sex and Patient-Reported Outcomes

Abstract: Background: Ischemic stroke (IS) is a leading cause of long-term disability with sex-specific differences in outcomes. Identifying the influential factors that contribute to sex-specific disparities in stroke outcomes, therefore, holds potential to develop individualized interventions for reducing long-term disability. Further, investigating the association between sex and Patient-Reported Outcome Measures (PROMs) provides additional information on the individual impact and heterogeneity of IS. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…27 Our prior research, examining stroke outcomes in both sexes, revealed that a mRS score of 2 or higher was associated with poorer T mental scores in both sexes. 28 However, additional work is needed to enhance our understanding of the complimentary information between mRS and PROMs.…”
Section: Discussionmentioning
confidence: 99%
“…27 Our prior research, examining stroke outcomes in both sexes, revealed that a mRS score of 2 or higher was associated with poorer T mental scores in both sexes. 28 However, additional work is needed to enhance our understanding of the complimentary information between mRS and PROMs.…”
Section: Discussionmentioning
confidence: 99%